Personality traits and aggressive behaviors: The mediating role of revenge - Cataldo, Quésia Fernandes (2019)
This study aims to verify the mediating role of revenge in the relationship between personality traits and aggression. The participation of 218 people, aged between 18 and 69 years (M=27.84; SD=10.37), mostly female and with incomplete higher education. Participants responded to the Big Five inventory, Buss-Perry aggression questionnaire and revenge scale. As a result, only kindness and neuroticism showed significant correlations with aggression factors and revenge. Regarding mediation, in kindness it was observed that the models of mediation are not adjusted to the data for physical, verbal aggression and hostility; In neuroticism, there was a partial mediation in all types of aggression. It is understood that the results contribute to the understanding of what mechanisms underlie aggressive behaviors, especially when taking into account personality traits and vengeful attitudes.